Efficient Solving of Boundary Value Problems Using Radial Basis Function Networks Learned by Trust Region Method - Mohie Mortadha Alqezweeni; Vladimir Ivanovich Gorbachenko; Maxim Valerievich Zhukov; Mustafa Sadeq Jaafar (International Journal of Mathematics and Mathematical Sciences)
A method using radial basis function networks (RBFNs) to solve boundary value problems of mathematical physics is presented in this paper. The main advantages of mesh-free methods based on RBFN are explained here. To learn RBFNs, the Trust Region Method (TRM) is proposed, which simplifies the process of network structure selection and reduces time expenses to adjust their parameters. Application of the proposed algorithm is illustrated by solving two-dimensional Poisson equation.